UJI DAYA TERIMA STIK IKAN KEMBUNG YANG DIMODIFIKASI DENGAN TEPUNG BAYAM HIJAU SEBAGAI CEMILAN SEHAT TINGGI ZAT BESI BAGI IBU HAMIL - Detaq, Beatrix; Niron, Maria FVDP Kewa; Hasan, Tobianus (Kupang Journal of Food and Nutrition Research, 2024)
Anemia that occurs in pregnant women is a condition where there is a lack of red blood cells in the blood circulation or hemoglobin (Hb) so that they cannot carry out their function in carrying oxygen properly. One of the triggers for pregnant women experiencing anemia is a lack of intake of foods rich in iron. One food ingredient that is high in iron is spinach. Spinach can be processed into a main dish or snack that pregnant women like. Spinach preparations that can be given to pregnant women are mackerel fish sticks prepared with the addition of spinach flour. It is hoped that mackerel fish sticks with the addition of spinach flour will be liked and help pregnant women meet their daily iron needs. Research Objectives: The aim of this research is to determine the effect of adding green spinach flour on the acceptability of mackerel fish sticks. Type of Research: This research is an experimental research using a Completely Randomized Design (CRD) with 4 treatment levels where 1 treatment uses the original recipe and 3 treatments use the addition of green spinach flour where at P1 20%, P215%, and P3 10%. From the results of the research conducted, the most preferred treatment in terms of color, aroma, texture and taste was P1 (adding 20% ​​spinach flour).